Metabolic effect of low fluoride levels in the islets of NOD mice: integrative morphological, immunohistochemical, and proteomic analyses (Journal of Applied Oral Science, 2023)
Fluoride (F) has been widely used to control dental caries, and studies suggest beneficial effects against diabetes when a low dose of F is added to the drinking water (10 mgF/L). Objectives: This study evaluated metabolic changes in pancreatic islets of NOD mice exposed to low doses of F and the main pathways altered by the treatment. Methodology: In total, 42 female NOD mice were randomly divided into two groups, considering the concentration of F administered in the drinking water for 14 weeks: 0 or 10 mgF/L. After the experimental period, the pancreas was collected for morphological and immunohistochemical analysis, and the islets for proteomic analysis. Results: In the morphological and immunohistochemical analysis, no significant differences were found in the percentage of cells labelled for insulin, glucagon, and acetylated histone H3, although the treated group had higher percentages than the control group. Moreover, no significant differences were found for the mean percentages of pancreatic areas occupied by islets and for the pancreatic inflammatory infiltrate between the control and treated groups. Proteomic analysis showed large increases in histones H3 and, to a lesser extent, in histone acetyltransferases, concomitant with a decrease in enzymes involved in the formation of acetyl-CoA, besides many changes in proteins involved in several metabolic pathways, especially energy metabolism. The conjunction analysis of these data showed an attempt by the organism to maintain protein synthesis in the islets, even with the dramatic changes in energy metabolism. Conclusion: Our data suggests epigenetic alterations in the islets of NOD mice exposed to F levels comparable to those found in public supply water consumed by humans.